International cooperation in public health in Martinique: geostrategic utility for cancer surveillance in the Caribbean - Clarisse Joachim; Thierry Almont; Moustapha Drame; Cédric Contaret; Mylène Vestris; Fatiha Najioullah; Aude Aline-Fardin; Patrick Escarmant; Nicolas Leduc; Nathalie Grossat; Xavier Promeyrat; Stefanos Bougas; et al. (BMC, 2020)
Abstract Background Cooperation in public health and in oncology in particular, is currently a major issue for the island of Martinique, given its geopolitical position in the Caribbean region. The region of Martinique shares certain public health problems with other countries of the Caribbean, notably in terms of diagnostic and therapeutic management of patients with cancer. We present here a roadmap of cooperation priorities and activities in cancer surveillance and oncology in Martinique. Main body The fight against cancer is a key public health priority that features high on the regional health policy for Martinique. In the face of these specific epidemiological conditions, Martinique needs to engage in medical cooperation in the field of oncology within the Caribbean, to improve skills and knowledge in this field, and to promote the creation of bilateral relations that will help to improve cancer management in an international healthcare environment. Conclusions These collaborative exchanges will continue throughout 2020 and will lead to the implementation of mutual research projects across a larger population basin, integrating e-health approaches and epidemiological e-cohorts.